Matematyka

Autorzy:Karolina Wej, Wojciech Babiański, Ewa Szmytkiewicz, Jerzy Janowicz

Wydawnictwo:Nowa Era

Rok wydania:2016

Rozwiąż równanie. a) (x-2)(x+1)=x²-3x 4.25 gwiazdek na podstawie 8 opinii
  1. Gimnazjum
  2. 2 Klasa
  3. Matematyka

`a) \ \ (x-2)(x+1)=x^2-3x` 

`x^2+x-2x-2=x^2-3x` 

`x^2-x-2=x^2-3x \ \ \ \ \ \ \ |-x^2` 

`-x-2=-3x \ \ \ \ |+x` 

`-2=-2x \ \ \ \ \ |:(-2)` 

`1=x` 

`x=1` 

`b) \ \ (x+2)(x-1)=x^2+8x` 

`x^2-x+2x-2=x^2+8x` 

`x^2+x-2=x^2+8x \ \ \ \ \ \ |-x^2` 

`x-2=8x \ \ \ \ \ |-8x` 

`-7x-2=0 \ \ \ \ \ \ \ |+2` 

`-7x=2 \ \ \ \ \ \ \ |:(-7)` 

`x=-2/7` 

`c) \ \ (2x+3)(2x-4)-2(x-3)(2x+1)=5`

`4x^2-8x+6x-12-2(2x^2+x-6x-3)=5` 

`4x^2-2x-12-2(2x^2-5x-3)=5` 

`4x^2-2x-12-4x^2+10x+6=5` 

`8x-6=5 \ \ \ \ \ \ \ \ |+6` 

`8x=5+6` 

`8x=11 \ \ \ \ \ \ \ \ \ \ \ \ |:8` 

`x=11/8=1 3/8` 

`d) \ \ x^2-(x-5)(2+x)=(x+4)(1-3x)+3x^2` 

`x^2-(2x+x^2-10-5x)=x-3x^2+4-12x+3x^2` 

`x^2-(-3x+x^2-10)=4-11x` 

`x^2+3x-x^2+10=4-11x` 

`3x+10=4-11x \ \ \ \ \ \ |+11x` 

`14x+10=4 \ \ \ \ |-10` 

`14x=-6 \ \ \ \ \ \ \ \ |:14` 

`x=-6/14=-3/7`